Cobalt oxide and N-doped carbon nanosheets derived from a single two-dimensional metal–organic framework precursor and their application in flexible asymmetric supercapacitors - Guan, Cao (2017)
Based on a new “one for two” strategy, a single two-dimensional (2D) metal–organic framework (MOF) precursor has been transformed into both electrodes (i.e., a Co3O4 cathode and a N-doped carbon anode) for a flexible asymmetric supercapacitor. The device demonstrated not only highly robust mechanical flexibility but also outstanding electrochemical performance. The “one for two” concept can significantly ease the fabrication process and has great potential to be extended to other functional materials for different applications.